The safety and efficacy of neutral electrolyzed water solution for wound irrigation: post-market clinical follow-up study - Valdová, Veronika; Štěpánová, Vladimíra; Lapčíková, Lenka (Frontiers in Drug Safety and Regulation, 2025)
IntroductionChronic wounds are a significant public health challenge, representing a considerable burden on the healthcare system. There are numerous gaps in knowledge in the treatment of chronic wounds. First, it is difficult to follow patients through different types of care. Wounds in polymorbid, elderly patients often remain unhealed due to the patient succumbing to their primary disease. No reliable data exist regarding the time to wound closure, type of interventions, the use of antibiotics, the nature and rate of complications, or the causes of treatment failures.MethodsThis Post-Market Clinical Follow-Up (PMCF) study is a prospective, multicentric, observational, descriptive, qualitative survey among healthcare professionals that involves 237 patients with acute and chronic wounds treated with superoxide-based wound irrigation solution DebriEcaSan Alfa in real-world settings over 12 weeks, both outpatient and inpatient. The study aimed to collect additional clinical data to confirm the safety, performance, and clinical benefit of DebriEcaSan Alfa.ResultsThe Manufacturer collected 237 survey forms from 81 healthcare facilities, nursing homes, and outpatient clinics in the Czech Republic. The most common diagnoses were venous leg ulcer, pressure ulcer, diabetic foot ulcer, and traumatic wound. The most common comorbidities and risk factors were obesity, diabetes mellitus, and peripheral artery disease. Significant improvement was observed in all parameters, including pain, malodor, affected tissues, reduction in wound size, and granulation and epithelization. A marked reduction in size was observed in all wound size categories. 19 (8%) patients healed by end of week 6; and 66 (28%) healed by week 9. 130 (55%) patients were considered healed by week 12.DiscussionThe current clinical practice guidelines refrain from recommending any of the available irrigation solutions and wound dressings due to low-quality evidence. Superoxidized solutions have excellent biocompatibility and are non-cytotoxic, non-sensitizing, not irritating, non-genotoxic, and have broad-spectrum antimicrobial properties. There is no objective baseline to compare the results to, as typical healing times in a comparable population are not accessible. No single standard of care exists in the treatment of chronic wounds, and significant variability in practices exists across the health system.